2011
DOI: 10.1002/pc.21159
|View full text |Cite
|
Sign up to set email alerts
|

Poly(lactic acid)/Phormium tenax composites: Morphology and thermo‐mechanical behavior

Abstract: Composites of Phormium tenax fibers in a poly(lactic acid) matrix with fiber content of up to 40 wt%, produced by injection molding and twin screw compounding, were characterized by scanning electron microscopy, differential scanning calorimetry, thermogravimetric analysis, and mechanical tests (static and dynamic). Thermal analysis showed that cold-crystallization peak shifted to lower temperatures with increasing fiber content, confirming that the addition of Phormium fiber has the effect of promoting crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 42 publications
4
24
0
Order By: Relevance
“…63 MPa, whereas a slight increase in Young modulus and a slight decrease in the elongation at break is noticed with the incorporation of 10 wt% of cellulose fibres. This trend is commonly observed with biocomposites PLA/natural fibres [43,56,57]. As shown in Table 5, at similar content of hemp fibres in PLA, Masirek et al [28] noticed a decrease in the elongation at break (-38%) and in the strength at yield (-23%).…”
Section: Thermal Propertiesmentioning
confidence: 59%
“…63 MPa, whereas a slight increase in Young modulus and a slight decrease in the elongation at break is noticed with the incorporation of 10 wt% of cellulose fibres. This trend is commonly observed with biocomposites PLA/natural fibres [43,56,57]. As shown in Table 5, at similar content of hemp fibres in PLA, Masirek et al [28] noticed a decrease in the elongation at break (-38%) and in the strength at yield (-23%).…”
Section: Thermal Propertiesmentioning
confidence: 59%
“…The Young's moduli and tensile strengths of 20 wt % harakeke are also greater than those for hemp composites of the same fibre content. This could be due to harakeke fibre being finer and typically having a better aspect ratio than hemp [22]. Figure 9 shows the effect of increasing fibre content on tensile strength in comparison with plain PLA for printed samples.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The recent study of their thermal and mechanical behavior indicated okra fibers as a possible candidate for use in the production of biodegradable composites 18 also in view of the maximum length of the extracted fibers, which is in excess of 60 cm. The recent study of their thermal and mechanical behavior indicated okra fibers as a possible candidate for use in the production of biodegradable composites 18 also in view of the maximum length of the extracted fibers, which is in excess of 60 cm.…”
Section: Introductionmentioning
confidence: 99%